Changing behavioral responses to heat risk in a warming world: How can communication approaches be improved?. (9th January 2023) - McLoughlin, Niall; Howarth, Candice; Shreedhar, Ganga
Abstract: Heat risks, such as those associated with heatwaves, are increasing in frequency, severity, and duration due to climate change. The ways in which people around the globe perceive and respond to heat risks are now of great importance to reduce a range of negative health outcomes. A growing body of literature aims to assess the factors that influence people's behaviors in relation to heat risks. This research can inform better interventions, such as improved communications approaches, that attempt to facilitate adaptive behavioral responses to such risks. This review focuses on how insights from behavioral and attitudinal studies about heat risk responses can inform communication approaches. These insights are organized into three key themes: (1) Behaviors —What types of actions can be taken by people, and what evidence is there for adaptive behavior? (2) Antecedents —Which individual and contextual factors can influence people's behaviors? (3) Communications —How can existing insights be better integrated into interventions? Aspects of communication, including the role of message characteristics, messenger, and imagery, are discussed, with examples of messages and narratives that target influential antecedents of adaptive responses to heat risks. The paper makes three important contributions. First, it organizes literature on the antecedents and behavioral responses to heat risk; second, it provides a typology of the range of heat risk behaviors; and, third, it discusses how antecedents can be integrated into communication interventions. The review concludes with a proposed agenda for research, highlighting the need for substantial testing and evaluation of heat risk communication, applying insights from the literature. This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication Perceptions, Behavior, and Communication of Climate Change > Behavior Change and Responses Abstract : Three spheres framework of heat risk behavior. The center "behavioral" sphere: actions that can be taken in response to heat risks. The middle, "individual" sphere: personal, affective and cognitive antecedents of heat risk behavior. The outer "contextual" sphere: contextual factors influencing the "individual" and "behavioral" layers.